Endothelium-derived hyperpolarising factor in the human forearm circulation. (22nd September 2015) - Ozkor, MA; Murrow, JR; Rahman, A; Kavtaradze, N; Aznaouridis, K; Lin, J; Manatunga, A; Halcox, J; Quyyumi, AA
Abstract : Background: Endothelium-derived hyperpolarising factor (EDHF) contributes to non-nitric oxide (NO)-mediated vasodilator tone by activating calcium-dependent potassium channels (K +ca ) that can be inhibited by tetraethylammonium. We explored the contribution of EDHF to (1) resting vasomotor tone; (2) endothelium-dependent agonist-mediated; and (3) physiologically stimulated increases in forearm blood flow (FBF), with the hypothesis that its contribution is altered in hypercholesterolaemic/diabetic states and in black compared with white individuals. Methods: In 96 healthy and 64 healthy control subjects with or without diabetes, we measured FBF during intra-arterial infusions of acetylcholine and bradykinin, during handgrip exercise, and after endothelium-independent vasodilation with sodium nitroprusside. Responses were measured before and after NO blockade with l -N G monomethyl arginine (l -NMMA), K +ca blockade with tetraethylammonium and cytochrome P450-dependent epoxyeicosatrienoic acids (EET) blockade with fluconazole. Results: L -NMMA and tetraethylammonium reduced resting FBF by 29% and 13%, respectively, in healthy subjects, with similar HC responses, indicating a greater contribution of NO compared with K +ca channel activation to resting vasodilator tone. Fluconazole did not change resting FBF in healthy subjects, but reduced FBF by 17% (p = 0.028) in dyslipidaemic subjects with diabetes, indicating a greater contribution of EET to resting vasodilator tone in diabetes. Both l -NMMA and tetraethylammonium attenuated bradykinin-mediated vasodilation to a similar extent in healthy and HC subjects, indicating a NO and K +ca channel contribution to bradykinin-mediated vasodilation. In contrast, tetraethylammonium had no effect on acetylcholine-mediated vasodilation in healthy subjects but significantly attenuated acetylcholine-mediated vasodilation in HC (fig 1 ). Thus, acetylcholine only stimulates the release of NO in healthy subjects, NO release is attenuated in HC in whom K +ca channel activation maintains acetylcholine-mediated vasodilation. Forearm vasodilation during exercise in healthy and HC subjects was attenuated by both l -NMMA and tetraethylammonium indicating contribution of both NO and EDHF. Bradykinin and sodium nitroprusside-mediated forearm vasodilation was greater in white compared with black individuals (p = 0.04 and p<0.01, respectively) due to a greater contribution of NO (response to l -NMMA) in whites. The response to tetraethylammonium was similar in both (fig 2 ), indicating a reduced sensitivity of the smooth muscle cells to NO in blacks. Conclusions: EDHF, measured as K +ca channel activation contributes to resting tone, exercise-induced vasodilation and bradykinin but not acetylcholine-mediated vasodilator tone of the healthy human microvasculature. The reduced bioavailability of NO in the HC microcirculation is accompanied by increased activity of K +ca channels. Thus, vasodilation in NO-deficient states appears to be maintained by increased EDHF activity. Ethnic differences in endothelium-dependent vasodilation are due to reduced bioavailability of NO and reduced sensitivity of smooth muscle cells to NO in blacks.